SKIN DISEASES PREDICTION USING DEEP LEARNING TECHNIQUES (CAHIERS MAGELLANES-NS, 2024)
Dermatological conditions have a substantial impact on the well-being of a large number of persons, since almost everyone experiences different types of skin disorders annually. Given the time-consuming and labor-intensive process of human analysis for these illnesses, along with the limited capability of current techniques to analyze specific types of skin diseases, there is a requirement for advanced computer-aided proficiency in the analysis and diagnosis of various skin diseases. This study lays out a procedure for real-time skin disease prediction that makes use of computer-assisted techniques including data mining algorithms and the CNN algorithm. When contrasted with other approaches, this strategy provides a more precise result.